Capital structure and its determinants - a comparison of European top-rated CSR and other companies - Peter Krištofík; Juraj Medzihorský; Hussam Musa (Journal of Risk and Financial Management, 2022)
Corporate social responsibility (CSR), ethics, and sustainability have become an inseparable part of the discourse of modern business. Applying linear regression and comparison of intervals of beta-coefficients, we focused on the mediating role of CSR in the relations between capital structure and its determinants. Examining the sample of European large caps, we observed that CSR companies are significantly more leveraged than non-CSR ones. The influence of the corporate income tax rate and depreciation and amortization on leverage does not differ significantly between CSR and non-CSR companies. Moreover, tax shields seem to be insignificant for both CSR and non-CSR companies. However, we should stress that, for depreciation and amortization, the beta coefficient has a different significance in the model of CSR companies, compared to the model of non-CSR companies. Also, the difference between the models regarding the relations of leverage and asset tangibility is worth noting. Non-CSR companies with a higher proportion of fixed assets have lower leverage. This result was not confirmed for CSR companies. The hypothesis that CSR replaces the role of collateral cannot be confirmed. Available cash influences leverage negatively in both models, supporting the pecking-order theory. This result is much stronger for non-CSR companies compared to CSR ones. This study found fewer statistically significant differences between CSR and non-CSR companies regarding capital structure determinants than were expected.
Keywords: 650; capital structure; behavioral finance; corporate social responsibility; leverage; non-financial companies